Risk Factors Associated with Post-COVID-19 Conditions Among Diabetes Patients in the United Arab Emirates - Aysha Alkhemeiri; Ziad El-Khatib; Abrar Hassan Alameri; Athari Ahmed AlKaabi; Jeyaseelan Lakshmanan; Niyi Awofeso (Journal of Epidemiology and Global Health)
Abstract Background A substantial subset of individuals recovering from the Coronavirus disease 2019 (COVID-19) continues to experience persistent symptoms. Individuals with type 2 diabetes face increased morbidity and mortality following COVID-19 infection. This study aimed to identify risk factors for developing post-COVID-19 conditions among COVID-19 patients with diabetes compared to those without diabetes in the United Arab Emirates. Methods A retrospective study was conducted on a random sample of 400 patients with confirmed COVID-19 (n = 200/400 patients with diabetes versus n = 200 patients without diabetes). Participants were invited to a telephone interview to assess post-COVID-19 symptoms persisting for at least three months after their initial positive COVID-19 polymerase chain reaction (PCR) test. A total of 167 hospitalized patients participated, including 89 with pre-existing diabetes and 78 without diabetes. Results The prevalence of self-reported post-COVID-19 conditions among participants with diabetes was 34.9%, compared to 14.1% among those without diabetes. Patients with diabetes reported a significant decline in functional status post-COVID-19, with 34.8% experiencing impaired physical activity and 32.6% reporting pain and discomfort, compared to 15.4% and 11.5%, respectively, among participants without diabetes. Older age and female gender were associated with a higher prevalence of post-COVID-19 conditions in the diabetes group. Conclusion Patients with diabetes in this study self-reported a higher frequency and severity of post-COVID-19 conditions compared to those without diabetes. Risk factors predisposing to severe post-COVID-19 conditions included female gender, older age, and comorbidities. Self-reported depression was rare in both groups of this cohort.